C–C Bond Activations of Minimally Activated Cyclopropanes - Sokolova, Olga O.; Dalling, Andrew G.; Bower, John F. (Synlett, 2022)
Catalytic processes involving oxidative addition of a C–C bond to a transition metal allow the atom economical assembly of complex scaffolds. The focus of this Account is on C–C bond activation-based methodologies that employ minimally activated cyclopropanes.
Keywords: C–C bond activation; oxidative addition; cyclopropanes